Using the chinese experience of accreditation of development companies and construction objects in state housing programs of reconstruction of Ukraine as an example of the "eOselya" program. - ZELTSER, Yevgen (Ways to Improve Construction Efficiency, 2024)
The need to provide housing for the citizens of Ukraine has become acute since Ukraine gained independence. The amounts of funds allocated by the state for housing construction and financing of state housing programs are extremely insufficient. Thus, according to the new state housing program "eOselya" in Diya, the operator of which is PJSC "UKRFINZHYTLO", in total, in 2022-2024, only 14.4 thousand families received an affordable mortgage and purchased their own housing at the expense of issued mortgage loans in the amount of UAH 23.3 billion. Since the beginning of hostilities, this problem has become even more urgent. As of January 2024 the total amount of only documented losses in residential and non-residential real estate, as well as other infrastructure of Ukraine is more than $135 billion. In total, as a result of hostilities, more than 203,000 high-rise buildings and private houses were destroyed or damaged. As a result, the main expenses in the housing sector are related to additional expenses of citizens for renting housing and reached $15.4 billion. Considering the fact that "eOselya" is one of the key tools for stimulating housing construction and the work of the construction market of Ukraine in general, the main emphasis in the program is on the primary market, the activation of housing construction, which in turn will stimulate the development of related industries. That is why it is urgent to solve all problematic issues that prevent the involvement of as many development companies as possible to participate in the program. One of these issues is the need for the partner banks of UKRFINZHYTLO to improve the accreditation procedure for development companies and construction projects. Therefore, it is clear that at the present time, state policy measures aimed at the development and reform of state housing programs, which must take into account the existing global experience of providing citizens with housing, are becoming particularly relevant. It is proposed to study China's experience in state regulation of the real estate market and ways of its use in Ukraine, in particular in matters of accreditation procedure for development companies and construction projects in state housing programs. A comprehensive solution to the problematic issue of accreditation procedure for development companies and construction projects by partner banks, taking into account the existing Chinese experience, will contribute to the involvement of as many high-quality, stably working development companies as possible to participate in state housing programs, in particular the "eOselya" program. This will make a significant contribution to the successful reform of state housing programs in Ukraine in the context of the country's reconstruction during and after the end of the full-scale war with russia.